Evaluation of toxicity of some biocompatible insecticides on Trichogramma brassicae and T. evanescens under laboratory and semi-field conditions - Sedighe Ashtari; Qodratollah Sabahi; Khalil Talebi Jahromi (Journal of Crop Protection, 2018)
The effects of four insecticides, abamectin (1500 and 750mgl-1), emamectin benzoate (1000 and 500mgl-1), acetamiprid (500 and 250mgl-1), and flubendiamide (500 and 250mgl-1), were studied on different preimaginal stages of T. brassicae and T. evanescens, the egg parasitoids of tomato leaf miner Tuta absoluta (Lepidoptera: Gelechiidae). Parasitized eggs of the Angoumois grain moth Sitotroga cerealella (Lepidoptera: Gelechiidae) were treated by the dipping method at the larval, prepupal, and pupal stages of the parasitoid. For persistence evaluation, the insecticides were applied at the recommended concentration on tomato plants by a hand sprayer till runoff point. Plants were maintained under a transparent polyethylene rain cover in the field. Leaves of the treated tomato plants were sampled and transferred to the laboratory at time intervals of 3, 5, 16, and 31 days after application. Based on our study, abamectin was the most harmful insecticide for immature stages of both parasitoids T. brassicae and T. evanescence. Treatment by abamectin at the pupal stage had more adverse effects compared to prepupal or larval stages. Acetamiprid with 30.5% and 31.6% mortality in less than five days was classified as the short-lived insecticide for T. brassicae and T. evanescens, respectively. The same result was obtained in flubendiamide treatment which caused 27.2% and 26.1% mortality to the parasitoids, respectively. Abamectin with 16.1% and 13.8% mortality in less than 16 days was slightly persistent. However, emamectin benzoate with 13.3% and 15.5% mortality in less than 30 days was classified as moderately persistent for those two species, respectively. Therefore, flubendiamide and acetamiprid were non-harmful to both T. brassicae and T. evanescence wasps and are good candidates to be incorporated into IPM programs in combination with biological agents for the control of tomato leaf miner T. absoluta. By contrast, emamectin and abamectin should be used with greater care as a part of an IPM procedure.